Staff Development Modifications Necessary to Increase Teacher Readiness for Change to Common Core State Standards - Kirsten Limpert (The Advocate, 2015)
Staff development is a crucial piece for successful implementation of the Common Core State Standards (CCSS). A complete plan must be developed that focuses on implementation of the Common Core State Standards. The focus for this plan should be on teacher needs with an aim to improve student learning. If teacher needs are considered and they see the value for their students, teachers will be more likely to not only accept this change but become actively involved in planning for implementation of CCSS.